La città del Genio. Leonardo a Milano (Materiali di Estetica. Terza serie, 2020)
A quick but punctual survey of the main “places” of Leonardo’s Milan that helps to reconstruct the actual concreteness of Leonardo da Vinci’s historical presence in the Lombard capital.
Keywords: Leonardo; Milan; Leonardo's city